2016
DOI: 10.4081/ijfs.2016.5879
|View full text |Cite
|
Sign up to set email alerts
|

Differences in chemical, physical and microbiological characteristics of Italian Burrata cheeses made in artisanal and industrial plants of the Apulia Region

Abstract: The burrata cheese is a traditional product from Southern Italy, consisting of an envelope of pasta filata (stretched curd) filled with cream and pasta filata strips (usually leftovers from mozzarella production). Physical [water activity (aw), pH], chemical (moisture, NaCl content) and microbiological [total viable count (TVC), Listeria monocytogenes, Salmonella spp., Yersinia enterocolitica, Bacillus cereus, Escherichia coli, Enterobacteriaceae, coagulase-positive staphylococci] characteristics of burrata ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 10 publications
4
18
2
Order By: Relevance
“…Differently, the concentrations in Ex-So and So remained almost constant during time. Increase in VOC formation during storage was expected, considering the typical chemical and microbiological characteristics of the product [ 27 , 30 , 31 ], and from these quantitative data it clearly appeared that a significant inhibition of their formation was associated to the presence of sorbic acid. In order to better understand the mechanisms of formation, the entire VOC data set was grouped into seven chemical classes ( Table 2 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Differently, the concentrations in Ex-So and So remained almost constant during time. Increase in VOC formation during storage was expected, considering the typical chemical and microbiological characteristics of the product [ 27 , 30 , 31 ], and from these quantitative data it clearly appeared that a significant inhibition of their formation was associated to the presence of sorbic acid. In order to better understand the mechanisms of formation, the entire VOC data set was grouped into seven chemical classes ( Table 2 ).…”
Section: Resultsmentioning
confidence: 96%
“…Only little shelf-life extension was obtained by Gammariello et al [ 28 ], by applying modified atmosphere packaging (MAP), and by Conte et al [ 29 ] combining it with two antimicrobial compounds (lysozyme and EDTA). Dambrosio et al [ 30 ] and Rea et al [ 31 ] concluded that the principal obstacle lay in the manufacturing process that involves intense manipulation. Unfortunately, the stracciatella production process cannot be mechanized since it is impossible to reproduce the results obtained by the manual procedure (in particular the mozzarella shredding phase).…”
Section: Introductionmentioning
confidence: 99%
“…acidified milk without a starter culture and stretching in hot water (80 to 90°C) (4). The pasta filata is molded to form an open hollow cheese sphere.…”
mentioning
confidence: 99%
“…In addition, different ingredients are used depending on the producers (e.g., whey cream produced by spontaneous rising or ultrahigh temperature centrifuged cream and cheeses produced at artisanal or industrial levels) (7). These factors result in cheeses that differ in shape, sensory and safety features, and consequently, the shelf life (4,8). Psychrotrophic microorganisms (Pseudomonas spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation